Using DMPP with cattle manure can mitigate yield-scaled global warming potential under low rainfall conditions. (1st January 2023) - Guardia, Guillermo; Abalos, Diego; Mateo-Marín, Noemí; Nair, Drishya; Petersen, Søren O.
Abstract: Organic fertilisers can reduce the carbon (C) footprint from croplands, but adequate management strategies such as the use of nitrification inhibitors are required to minimise side-effects on nitrogen (N) losses to the atmosphere or waterbodies. This could be particularly important in a context on changing rainfall patterns due to climate change. A lysimeter experiment with maize ( Zea mays L.) was set up on a coarse sandy soil to evaluate the efficacy of 3, 4-dimethylpyrazole phosphate (DMPP) to mitigate nitrous oxide (N2 O) emissions, nitrate (NO3 − ) leaching losses and net global warming potential from manure, with (R+) and without (R-) simulated rainfall events. Soil water availability was a limiting factor for plant growth and microbial processes due to low rainfall during the growing season. Nitrification was effectively inhibited by DMPP, decreasing topsoil NO3 − concentrations by 28% on average and cumulative N2 O losses by 82%. Most of the N2 O was emitted during the growing season, with annual emission factors of 0.07% and 0.95% for manure with and without DMPP, respectively. Cumulative N2 O emissions were 40% higher in R-compared to R+, possibly because of the higher topsoil NO3 − concentrations. There was no effect of DMPP or rainfall amount on annual NO3 − leaching losses, which corresponded to 12% of manure-N and were mainly driven by the post-harvest period. DMPP did not affect yield or N use efficiency (NUE) while R-caused severe reductions on biomass and NUE. We conclude that dry growing seasons can jeopardize crop production while concurrently increasing greenhouse gas emissions from a sandy soil. The use of nitrification inhibitors is strongly recommended under these conditions to address the climate change impacts. Graphical abstract: Image 1 Highlights: DMPP (Vizura®) with cattle manure tested under low and normal rainfall conditions. Drier conditions increased N2 O losses without reducing NO3 − leaching. Vizura® mitigated N2 O emissions by 82% with no effect on NO3 − leaching. Low rainfall resulted in severe yield and NUE penalties. Vizura® lessened area-scaled and yield-scaled GWP through N2 O loss abatement.